Chlorination treatment of aqueous samples reduces, but does not eliminate, the mutagenic effect of the azo dyes Disperse Red 1, Disperse Red 13 and Disperse Orange 1 - Oliveira, G. A. R.; Ferraz, E. R. A.; Chequer, F. M. D.; Grando, M. D.; Angeli, J. P. F.; Tsuboy, M. S.; Marcarini, J. C.; Mantovani, M. S.; Osugi, M. E. [UNESP]; Lizier, T. M. [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Oliveira, D. P. (Elsevier B.V., 2010)
The treatment of textile effluents by the conventional method based on activated sludge followed by a chlorination step is not usually an effective method to remove azo dyes, and can generate products more mutagenic than the untreated dyes. The present work evaluated the efficiency of conventional chlorination to remove the genotoxicity/mutagenicity of the azo dyes Disperse Red 1, Disperse Orange 1, and Disperse Red 13 from aqueous solutions. The comet and micronucleus assays with HepG2 cells and the Salmonella mutagenicity assay were used. The degradation of the dye molecules after the same treatment was also evaluated, using ultraviolet and visible absorption spectrum measurements (UV-vis), high performance liquid chromatography coupled to a diode-array detector (HPLC-DAD), and total organic carbon removal (TOC) analysis. The comet assay showed that the three dyes studied induced damage in the DNA of the HepG2 cells in a dose-dependent manner. After chlorination, these dyes remained genotoxic, although with a lower damage index (DI). The micronucleus test showed that the mutagenic activity of the dyes investigated was completely removed by chlorination, under the conditions tested. The Salmonella assay showed that chlorination reduced the mutagenicity of all three dyes in strain YG1041, but increased the mutagenicity of Disperse Red 1 and Disperse Orange 1 in strain TA98. With respect to chemical analysis, all the solutions showed rapid discoloration and a reduction in the absorbance bands characteristic of the chromophore group of each dye. However, the TOC was not completely removed, showing that chlorination of these dyes is not efficient in mineralizing them. It was concluded that conventional chlorination should be used with caution for the treatment of aqueous samples contaminated with azo dyes. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Azo dye; Chlorination; Comet assay; Micronucleus assay; Salmonella assay